Pemetaan Jaringan Pendukung Transformasi Bisnis Digital Pada UMKM Disabilitas di Indonesia: Analisis Stakeholder Komprehensif - Moh. Ilham; Agus Hermawan; M. Adi Trisna Wahyudi (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
This article investigates the empowerment of Micro, Small, and Medium Enterprises (MSMEs) owned by individuals with disabilities through digital business transformation, with a specific focus on reviewing content creators on the YouTube platform. This analytical approach aims to understand how disabled MSMEs utilize digital platforms, particularly YouTube, to expand their reach, increase visibility, and gain support from the community. Data were collected through searching and analyzing content produced by creators related to disabilities and MSMEs, using the search method of the top 10 views from 3 hashtags #MSME #disability #digital. The findings from this analysis reveal the low intensity of the number of viewers with the highest views still below 1000, there are already some parties that have supported disabled MSMEs by involving various stakeholders, such as the government, financial institutions, non-profit organizations, academics, business associations, and surrounding communities. These findings not only reveal the strategies and best practices used by disabled MSMEs in utilizing YouTube but also highlight the challenges and opportunities they face in the process. Policy implications and recommendations to support the growth of disabled MSMEs through digital platforms are also discussed. This research is expected to provide a deeper insight into the role of digital business in strengthening economic inclusion for individuals with disabilities in Indonesia.